Analisis Pengendalian Persediaan Pada Hotel X Di Senggigi Lombok - Putriasih, Ni Putu Swasthyas; Yunita Putri, I Gusti Ayu; Rizki, Novia (Fakultas Ekonomi dan Bisnis Unram, 2025)
This study aims to analyze the inventory control process at Hotel X, a five-star hotel in the Senggigi tourist area, West Lombok. This study uses a qualitative approach to determine the role of receiving in the procedure of receiving, issuing goods and managing inventory in the warehouse in supporting the operations of Hotel X. Data in this study were collected through field observations andinterviews with related parties at the hotel, especially the receiving department. The results of the study indicate that Hotel X applies the Economic Order Quantity (EOQ) method to minimize storage costs and avoid excess or shortage of inventory and uses stewardship theory to provide an initial understanding of the process of incoming and outgoing goods in the warehouse. Inventory controlis carried out in a coordinated manner starting from the receiving, purchasing, to the upper management level, and uses a bin card recording system and the Power Pro application to support the accuracy of stock data. Inventory grouping is carried out based on departments such as food & beverage, housekeeping, and engineering to increase efficiency. The control system implementedhas proven effective in maintaining smooth hotel operations and supporting optimal guest service.